Community Sanctions as Substitutes to Imprisonment in the Nordic Countries - Lappi-Seppälä, Tapio (2014)
Vortex-induced vibrations (VIV) and wake interference on circular cylinders have reached a lot of research attention over the years. However, most research is done for relativly low Reynold numbers (sub-critical) and does not correspond to real world chimney situations. A real chimney in the south of Sweden has experienced some large vibrations and data gathered from this chimney shows a correlation between these motions and wind directions. Results from 2D CFD simulations used to simulate VIV on a circular cylinder when laying in the wake of another larger, and fix, cylinder at critical Reynold numbers are presented in this thesis. Simulations are done for three cases; one single cylinder, for comparisons, and two simluations for cylinders in tandem arrangement, at 35 and 70 m respectively. Results show that the cylinder when in tandem arrangement experience much larger vibrations than the single cylinder. For velocities above 10 m/s the tandem arrangement can lead to resonance on the cylinder, which is not occuring in the case with a single cylinder. This thesis shows that even at distances of 70 m, wake interference can have a large effect on VIV and more advanced models and simulations would be useful for better predictions of the behaivor of chimneys